Cryptocurrency: Concept, Global Scenario and Nepal – A Short Essay - Ghimire, Abhishek (Kalika Journal of Multidisciplinary Research, 2024)
In a world, witnessing an explosion of financial technology (fintech) innovations competing with traditional financial methods, cryptocurrencies and the blockchain technology underpinning them have made it difficult for the relevant socio-economic and legal modifications to keep pace with the needs of time. The legal rules that apply to cryptocurrency remain unclear and unsettled even after fifteen years of its emergence. Due to the fear that cryptocurrencies would hamper the traditional market infrastructures and break off the control of the government over the monetary system, countries like Nepal have out rightly banned them without any proper research. However, their adoption seems to be accelerating in the global economies to harness the potentialities of this baffling technology. This research employs qualitative research techniques to examine the regulatory frameworks adopted worldwide to address the concerns so that strategies may be designed that will improve the management of these financial innovations and establish a more secure environment in which it can persist because, in the end, the global economy is going to be digital.